The Influence of Good Corporate Governance on Company Value With Audit Quality as Moderating Variable - Pujiastuti, Heni (Dinasti Publisher, 2022)
This study will analyze the influence of Good Corporate Governance in determining the value of the company through the Independent Commissioner and the Board of Directors. As a moderating variable, audit quality is used as measured by a dummy variable on the use of big four auditors. The sample used includes 31 companies in the food and beverage industry sub-sector and the miscellaneous goods industry sub-sector listed on the Indonesia Stock Exchange for the 2018-2020 period which were selected by purposive random sampling. After the multiple linear regression test and hypothesis testing as well as the coefficient of determination test, the results show that the Independent Commissioner and the Board of Directors have no effect on firm value, because the value created does not provide a significant increase for stakeholders. The same thing also happened to audit quality with the result that there was no effect or weakening on the creation of Company Value because investors did not consider the name of the auditor as long as the audit report was published.